The neutralizing response to SARS-CoV-2 Omicron variants BA.1 and BA.2 in COVID-19 patients and homologous and heterologous vaccinees. Issue 6 (30th November 2022) - Dapporto, Francesca; Leonardi, Margherita; Trombetta, Claudia Maria; Semplici, Claudia; Piu, Pietro; Piccini, Giulia; Benincasa, Linda; Marchi, Serena; Andreano, Emanuele; Lovreglio, Piero; Buonvino, Nicola; Decaro, Nicola; et al.
ABSTRACT: The rapid replacement of Omicron BA.1 by BA.2 sublineage is very alarming, raising the question of whether BA.2 can escape the immunity acquired after BA.1 infection. We compared the neutralizing activity toward the Omicron BA.1 and BA.2 sub-lineages in five groups: COVID-19 patients; subjects who had received two doses of mRNA vaccine; subjects naturally infected with SARS-CoV-2 who had received two doses of mRNA; and subjects who had received three doses of homologous or heterologous vaccine. The results obtained highlight the importance of vaccine boosters in eliciting neutralizing antibody responses against Omicron sub-lineages, and suggest that the adenovirus vectored vaccine elicits a lower response against BA.1 than against BA.2 sub-lineage.